Beneficiary views on cash and in-kind payments: Evidence from Ethiopia’s productive safety net programme - Hirvonen, Kalle; Hoddinott, John F. (World Bank, 2020)
Economists often default to the assumption that cash is always preferable to an in-kind transfer. Do beneficiaries feel the same way? This paper addresses this issue using longitudinal household data from Ethiopia where a large-scale social safety net intervention (PSNP) operates. Even though most payments are made in cash, and even though the (temporal) transaction costs associated with food payments are higher than payments received as cash, most beneficiaries stated that they prefer their payments only or partly in food. Higher food prices induce shifts in stated preferences towards in-kind transfers. More food secure households, those closer to food markets and to financial services are more likely to prefer cash. Though shifts occur, the stated preference for food is dominant: In no year do more than 17 percent of households prefer only cash. There is suggestive evidence that stated preferences for food are also driven by self-control concerns.